Connexin 43 upregulation by dioscin inhibits melanoma progression via suppressing malignancy and inducing M1 polarization. Issue 8 (20th July 2017) - Kou, Yu; Ji, Liyan; Wang, Haojia; Wang, Wensheng; Zheng, Hongming; Zou, Juan; Liu, Linxin; Qi, Xiaoxiao; Liu, Zhongqiu; Du, Biaoyan; Lu, Linlin
Abstract : Connexin 43 (Cx43), a vital gap junction protein in tumor microenvironment (TME), is a novel molecular target for melanoma chemotherapeutics due to its tumor suppressive function. Dioscin, an herbal steroidal saponin, exerts anti‐tumor effects while the underlying mechanism is unclear. Using WB, FACS, and immunofluorescence methodologies, we found dioscin significantly activated the transcription and translation of Cx43 via the retinoid acid signaling pathway and simultaneously enhanced the transporting function of Cx43. Through stimulating Cx43, dioscin remarkably suppressed the migratory and invasive capacities of B16 cells, and notably decreased pluripotency markers of cancer stem cells and epithelial‐to‐mesenchymal transition in B16 cells and animal tumor tissues. Conversely, dioscin improved the secretion of pro‐inflammatory cytokines (IL‐6, TNFα, and IL‐1β), and the phagocytic capacity of tumor‐associated macrophages by increasing M2‐to‐M1 phenotype transition. More strikingly, even in Cx43 functional deficient B16 and RAW264.7 cells, dioscin still dramatically reversed the aggravated tumor malignancy and reduced macrophage phagocytic activity. Two classical metastasis animal models were utilized in vivo and results showed that dioscin showed significant anti‐metastatic effects, which is closely related to the expression of Cx43 either in in situ tumor or metastatic lung nodes. In conclusion, dioscin targets Cx43 to suppress the tumor cell malignancy and activate macrophage sensitivity, thereby targeting melanoma microenvironment. Abstract : What's new? New results reveal how an Chinese herbal medicine component acts against melanoma. Dioscin, a natural steroidal saponin, induces apoptosis in breast cancer as well as boosting production of pro‐inflammatory cytokines. These authors investigated the chemical's effect on connexin 43, a tumor suppressing protein found in the microenvironment that is frequently silenced in metastatic melanoma. Dioscin remarkably enhanced the expression of connexin 43, as well as boosting its ability to reverse the metastatic transition. Treatment with dioscin also enhanced the immune response, spurring macrophages to attack the tumor cells.